Growth differentiation factor 15 as a useful biomarker for mitochondrial disorders. Issue 5 (14th October 2015) - Yatsuga, Shuichi; Fujita, Yasunori; Ishii, Akiko; Fukumoto, Yoshihiro; Arahata, Hajime; Kakuma, Tatsuyuki; Kojima, Toshio; Ito, Masafumi; Tanaka, Masashi; Saiki, Reo; Koga, Yasutoshi
<x xml:space="preserve">Abstract</x> Objective The diagnosis of mitochondrial disorders (MDs) is occasionally difficult because patients often present with solitary, or a combination of, symptoms caused by each organ insufficiency, which may be the result of respiratory chain enzyme deficiency. Growth differentiation factor 15 (GDF‐15) has been reported to be elevated in serum of patients with MDs. In this study, we investigated whether GDF‐15 is a more useful biomarker for MDs than several conventional biomarkers. Methods We measured the serum levels of GDF‐15 and fibroblast growth factor 21 (FGF‐21), as well as other biomarkers, in 48 MD patients and in 146 healthy controls in Japan. GDF‐15 and FGF‐21 concentrations were measured by enzyme‐linked immunosorbant assay and compared with lactate, pyruvate, creatine kinase, and the lactate‐to‐pyruvate ratio. We calculated sensitivity and specificity and also evaluated the correlation based on two rating scales, including the Newcastle Mitochondrial Disease Rating Scale (NMDAS). Results Mean GDF‐15 concentration was 6‐fold higher in MD patients compared to healthy controls (2, 711 ± 2, 459 pg/ml vs 462.5 ± 141.0 pg/mL; p < 0.001). Using a receiver operating characteristic curve, the area under the curve was significantly higher for GDF‐15 than FGF‐21 and other conventional biomarkers. Our date suggest that GDF‐15 is the most useful biomarker for MDs of the biomarkers examined, and it is associated with MD severity. Interpretation Our results suggest that measurement of GDF‐15 is the most useful first‐line test to indicate the patients who have the mitochondrial respiratory chain deficiency. Ann Neurol 2015;78:Ann Neurol 2015;78:679–696